Domestication and crop evolution of wheat and barley: Genes, genomics, and future directions. Issue 3 (12th February 2019) - Haas, Matthew; Schreiber, Mona; Mascher, Martin
Abstract: Wheat and barley are two of the founder crops of the agricultural revolution that took place 10, 000 years ago in the Fertile Crescent and both crops remain among the world's most important crops. Domestication of these crops from their wild ancestors required the evolution of traits useful to humans, rather than survival in their natural environment. Of these traits, grain retention and threshability, yield improvement, changes to photoperiod sensitivity and nutritional value are most pronounced between wild and domesticated forms. Knowledge about the geographical origins of these crops and the genes responsible for domestication traits largely pre‐dates the era of next‐generation sequencing, although sequencing will lead to new insights. Molecular markers were initially used to calculate distance (relatedness), genetic diversity and to generate genetic maps which were useful in cloning major domestication genes. Both crops are characterized by large, complex genomes which were long thought to be beyond the scope of whole‐genome sequencing. However, advances in sequencing technologies have improved the state of genomic resources for both wheat and barley. The availability of reference genomes for wheat and some of its progenitors, as well as for barley, sets the stage for answering unresolved questions in domestication genomics of wheat and barley. Abstract : Genetic changes as a consequence of domestication or subsequent crop evolution were essential to the modification of wild cereals into forms useful to humans. The progenitors of wheat and barley serve as a reservoir for novel genes. Extensive sequence resources are now available to facilitate crop improvement from wild relatives.